Pengaruh Qawā’id Uṣūliyyah dan Fiqhiyyah terhadap Perbedaan Pendapat dalam Kasus Riba dan Bunga Bank - Nur'aeni, Ulvah (Institut KH Ahmad Sanusi (INKHAS) Sukabumi, 2022)
This paper highlights the influence of qawāid uṣūliyyah and fiqhiyyah in the disputation of interest law status. This controversy emerged when conventional banks faced Islamic banks that presented to offer financial systems instead of avoiding interest. The requirement of the Islamic bank is increasingly unstoppable because of the rise of religious consciousness that occurs in Indonesian Muslim society. Along with the need for a more secure and beneficial financial system for the people, the opinion difference on interest law has colored the development of Islam bank. The distinction of opinion affects the continuity of using conventional banks while Islam bank obviously presents among Muslim society. The difference in the legal fatwa of interest lies in the 'illat prohibition of usury in the level of takhrīj al-manāṭ, tanqīḥ al-manāṭ, and taḥqīq al-manāṭ. 'Illat includes extortion and abuse, additional without risk, and the addition of a double. On traditionalists, ‘illat of the interest prohibition is the addition, whether it is multiplied or not. Therefore, for this group bank interest is clearly forbidden. By contrast, the modernist relies on the 'illat of extortion and persecution. Consequently, if the interest borne by a person or an institution contains exploitation, then interest is haram and prohibited. The results of this study were obtained using descriptive analysis methods and based on a literature review.